Advances in oligonucleotide drug delivery - Roberts, TC; Langer, R; Wood, MJA (Springer Nature, 2020)
Oligonucleotides can be used to modulate gene expression via a range of processes including RNAi, target degradation by RNase H-mediated cleavage, splicing modulation, non-coding RNA inhibition, gene activation and programmed gene editing. As such, these molecules have potential therapeutic applications for myriad indications, with several oligonucleotide drugs recently gaining approval. However, despite recent technological advances, achieving efficient oligonucleotide delivery, particularly to extrahepatic tissues, remains a major translational limitation. Here, we provide an overview of oligonucleotide-based drug platforms, focusing on key approaches — including chemical modification, bioconjugation and the use of nanocarriers — which aim to address the delivery challenge.